1985
DOI: 10.1159/000466359
|View full text |Cite
|
Sign up to set email alerts
|

The Serology of Febrile Transfusion Reactions

Abstract: Sera from 40 patients with febrile, nonhemolytic transfusion reactions were tested for the presence of alloantibodies using a number of techniques, including immunofluorescence tests on granulocytes, lymphocytes and platelets, a modified NIH lymphocytotoxicity test and the leukocyte agglutination test. Cells of at least 9 donors were used as target cells. Alloantibodies were detected in all sera. The frequency of the occurrence of antibodies was not much higher in sera obtained about 1 month after the transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…They can be defined as rise of body temperature by 1 °C or more within the first 4 h of transfusion and normalization of the temperature within 48 h, if transfusion of a bacterially contaminated blood product can be excluded and if no signs of hemolysis are found [1,2]. Patients with isolated febrile reactions may otherwise be asymptomatic or may experience rigor and chills.…”
Section: Febrile Non-hemolytic Transfusion Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be defined as rise of body temperature by 1 °C or more within the first 4 h of transfusion and normalization of the temperature within 48 h, if transfusion of a bacterially contaminated blood product can be excluded and if no signs of hemolysis are found [1,2]. Patients with isolated febrile reactions may otherwise be asymptomatic or may experience rigor and chills.…”
Section: Febrile Non-hemolytic Transfusion Reactionsmentioning
confidence: 99%
“…In the patients studied by Decary et al [3], 64% of patients with nonhemolytic transfusion reactions had leukocyte antibodies as compared to 30% of control patients. De Rie et al [1] further characterized antibodies as human leukocyte antigen (HLA-), platelet-and granulocyte antibodies in patients with febrile reactions. HLA antibodies were the most common, followed by platelet antibodies and the least common granulocyte antibodies.…”
Section: Febrile Non-hemolytic Transfusion Reactionsmentioning
confidence: 99%
“…Another concern raised in reports of HLA antibodies causing reactions is that the presence of the HLA antibody may have obscured the simultaneous presence of another cell-specific antibody. This has been shown by de Rie et al [9] who demonstrated the presence of platelet-specific antibody in 12 of 40 sera containing HLA antibody by studying reaction patterns and performing absorption and elution studies. This pres ent report ruled out the presence of underlying neutrophil or platelet-specific antibody after removing lymphocyto toxic antibody by lymphocyte absorption and testing the absorbed sera against a panel of cells including those from the implicated donors.…”
Section: Discussionmentioning
confidence: 78%
“…Severe febrile and pulmonary reactions, sometimes fatal, have occurred with transfusions to patients with antibodies to antigenic determinants on red cells [1] and leukocytes [2][3][4][5][6][7][8][9]. Non hemolytic transfusion reactions have also occurred in the absence of detectable recipient antibody due to the pas sive transfusion of donor antibody reacting with the recipient's red cell [10,11], platelet [12,13], granulocyte [14,15] or HLA [16][17][18] antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Febrile nonhemolytic transfusion reactions may be caused by granulocyte-specific alloantibodies [27]. The relative importance of granulocyte, HLA class I and platelet antibodies is not quite as clear although HLA-specific antibodies were most often found associated with this kind of transfusion reaction [28]. Recent data suggest that many cases of febrile transfusion reaction to platelet concentrates may not be immunemediated but caused by cytokines produced by contaminating leukocytes during storage [29].…”
Section: Clinical Conditionsmentioning
confidence: 99%